Zapisz w jak najprostrzej postaci
a) 2x(x-5)-3(x²- 2x) +(x-2) x
b) a(a+b +c)- B(a-b+c)-c(a-b-c) - c( a-b-c)
Oblicz wartości liczbowe wyrażeń
a)3(x²- 2x+ 3) -2 (x² - 5x- 1) dla X= 2
b) a( 2ab + b) -b (a- 2ab + a²) dla a= 0,1 i b = - 10



DAM NAJ:)!!!!

2

Odpowiedzi

  • Użytkownik Zadane
2010-03-03T17:12:24+01:00
A) 2x(x-5)-3(x²- 2x) +(x-2) x=2x²-10x-3x²+6x+x²-2x= -6x

b) a(a+b +c)- B(a-b+c)-c(a-b-c) - c( a-b-c)=a²+ab+ac-ab+b²-bc-ac+bc+c²-ac+bc+c²=a²+b²+2c²-ac+bc


a)3(x²- 2x+ 3) -2 (x² - 5x- 1) = 3x²-6x+9-2x²+10x+2=x²+4x+11= 2²+4*2+11=4+8+11=23

b) a( 2ab + b) -b (a- 2ab + a²)= 2a²b+ab-ab+2ab²-a²b=a²b+2ab²= 0,1²*(-10)+2*0,1*(-10)²= 0,01*(-10)+20=-0,01+20=19,9
Najlepsza Odpowiedź!
2010-03-03T17:12:30+01:00
A)
2x(x-5)-3(x²- 2x) +(x-2) x=
2x²-10x-3x²+6x+x²-2x=
-6x

b)
a(a+b +c)- B(a-b+c)-c(a-b-c) - c( a-b-c)=
a²+ab+ac-ab+b²-bc-ac+bc+c²-ac+bc+c²=
a²+b²+2c²-ac+bc

Oblicz wartości liczbowe wyrażeń:
a)
3(x²- 2x+ 3) -2 (x² - 5x- 1) =
3x²-6x+9-2x²+10x+2 =
x²+4x+11 =
2²+4*2+11 =
4+8+11 =
23

b)
a( 2ab + b) -b (a- 2ab + a²) =
2a²b+ab-ab+2ab²-a²b =
a²b+2ab² =
0,1²*(-10)+2*0,1*(-10)² =
0,01*(-10)+0,2*100 =
-0,1+20 =
19,9
1 5 1